Modelling and analysis of an out-of-plane electret-based vibration energy harvester with AC and DC circuits. (June 2020) - Yang, Zhaoshu; Tang, Lihua; Yu, Liuding; Tao, Kai; Aw, Kean
Highlights: Theoretical models of electret vibration energy harvesters with AC and DC circuits are proposed. Approximate analytical solutions for the above theoretical models are derived and verified. The power loss of DC circuit due to reverse current of diodes is investigated for the first time. Abstract: An electret-based vibration energy harvester (eVEH) is a promising candidate to convert the environmental vibration into electricity efficiently. Although numerous researches exist on the structural design and applications of eVEHs, the analytical models for eVEHs to predict the outputs with different interface circuits are still lacking. In this paper, we endeavour to develop the theoretical methods to analyse the performance of eVEHs interfaced with both AC and DC circuits. Approximate analytical solutions for the models with AC and DC circuits are developed with harmonic balance method and Newton-Raphson harmonic balance method, respectively. The theoretical models and the derived approximate analytical solutions are verified by circuit simulation and experiment. The models could be utilized for estimating the steady-state performance of an eVEH without simulating the time-domain response and the power loss on diodes with different forward voltage drops and reverse current leakages in DC circuit are investigated theoretically and experimentally. The work of this paper could be utilized for theoretical analysis and optimal design of eVEHs in out-of-plane mode and set a milestone for developing more sophisticate interface circuits for eVEHs.